2019
DOI: 10.1111/cod.13247
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy and allergic contact dermatitis caused by lavender: A retrospective study from an Australian clinic

Abstract: Results:Among the 2178 patients patch tested with lavender over this period, a total of 58 positive reactions were recorded in 49 individuals, giving a positive patch test prevalence for patients tested with lavender of 2.2%. Twenty-seven patients were diagnosed with ACD. The most common sources of exposure to lavender were personal care products and essential oils.Of the patients with ACD, 74% were tested with lavender absolute, with positive results in 90% of cases.Conclusion: Lavender is an uncommon cause o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…Linalool, a fragrance terpene present in many cosmetics and household products, and a major component of lavender, is a well-known cause of (airborne) allergic contact dermatitis. 4,8,9 We report this case to highlight that electronic ultrasonic diffusers and "home-made" cosmetics and remedies may well be overlooked allergen sources of this sensitizer. 10 Moreover, this case illustrates that patch tests need to be considered in patients with (therapy-resistant) AD, and preferably before a systemic treatment is initiated.…”
Section: Discussionmentioning
confidence: 93%
“…Linalool, a fragrance terpene present in many cosmetics and household products, and a major component of lavender, is a well-known cause of (airborne) allergic contact dermatitis. 4,8,9 We report this case to highlight that electronic ultrasonic diffusers and "home-made" cosmetics and remedies may well be overlooked allergen sources of this sensitizer. 10 Moreover, this case illustrates that patch tests need to be considered in patients with (therapy-resistant) AD, and preferably before a systemic treatment is initiated.…”
Section: Discussionmentioning
confidence: 93%
“…For this reason, it is important to advise patients who are allergic to perfumes to avoid “natural” products. A recent study showed that the prevalence of contact allergy to lavender was 2.2%, and that the three most frequent concomitant positive reactions were to fragrance mix I, fragrance mix II, and Myroxylon pereirae resin . It is important to remember that the exposure to lavender could go unreported, because patients have the false belief that anything “natural” is “safe.”…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence appears to be lower in North America, with one study finding a 0.3% positivity rate [57]. A more recent Australian study reported a positive patch test prevalence of 2.2% [58], Occupational ACD to lavender has been reported in the literature. For example, a hairdresser presenting with hand dermatitis was found to have allergy to lavender oil that was present in the shampoo used at her workplace [59].…”
Section: And 2020 Updates To the American Contact Dermatitis Society mentioning
confidence: 99%